Doing physics with scientific notebook : a problem-solving approach - Gallant, Joseph (West Sessex: Wiley, 2012)
This guide provides step-by-step instructions to guide those using Scientific Notebook (SNB) software to deal with physics problems. Including a CD enabling the reader to have 30-day trial of SNB software, the book contains many examples with detailed explanations of how to use the features of SNB to solve many physics problems.
References 491-494p.; Index 495-505p.
Keywords: Mathematical physics; Data processing; Physics